2015
DOI: 10.3402/jchimp.v5.26332
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid follicular carcinoma presenting as metastatic skin nodules

Abstract: BackgroundFollicular thyroid cancer (FTC) metastasizes most commonly to the lungs and non-cranial bones. Skull and skin are uncommon sites and usually manifest well after the diagnosis of primary malignancy. Metastasis to skull and skin as the presenting feature of FTC is infrequently reported in the literature.Case presentationA 65-year-old Caucasian woman with a history of thyroid nodule presented with the complaint of rapidly growing skull nodules which had been present for 3 years but were stable previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In fact, Somoza et al reported a similar case, that of a 71-year-old Caucasian male with a skin metastasis of about 1 cm from a follicular variant of PTC (17), and Smit et al found a 79-year-old Caucasian woman with skin metastases as the first manifestation of a follicular variant of PTC (18). Jehangir et al also observed a Caucasian woman with a history of thyroid nodule who had rapidly growing skull nodules and a histological diagnosis of FTC (19), and Shamim et al published two case reports in which a skull lesion was the first manifestation (20). In all these cases, however, the skin lesions were far more advanced than in our case.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Somoza et al reported a similar case, that of a 71-year-old Caucasian male with a skin metastasis of about 1 cm from a follicular variant of PTC (17), and Smit et al found a 79-year-old Caucasian woman with skin metastases as the first manifestation of a follicular variant of PTC (18). Jehangir et al also observed a Caucasian woman with a history of thyroid nodule who had rapidly growing skull nodules and a histological diagnosis of FTC (19), and Shamim et al published two case reports in which a skull lesion was the first manifestation (20). In all these cases, however, the skin lesions were far more advanced than in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib was planned for palliative intent. Asad Jehangir et al reported a 65-year-old Caucasian woman with a history of thyroid nodule presented with the complaint of rapidly growing skull nodules which had been present for 3 years but were stable [20]. The prognosis is relatively poor in metastatic follicular thyroid carcinoma with 5 and 10 years mortality rates of approximately 60% and 80% respectively [10].…”
Section: Discussionmentioning
confidence: 99%
“…If tumour removal is less indicated in mentioned pituitary and adrenal incidentalomas, surgery for an incidental thyroid nodule is recommended depending on complex risk stratification strategy of approach (1,22,27). Incidental finding of a skin lump originating from a thyroid cancer remains an exceptional scenario (28,29,30). Whole body imagery evaluation may show the general metastatic context if positive or it may suggest the thyroid origin especially in patients with prior thyroidectomy and a certain disease free interval (28,29,30).…”
Section: Incidental Findingsmentioning
confidence: 99%
“…Incidental finding of a skin lump originating from a thyroid cancer remains an exceptional scenario (28,29,30). Whole body imagery evaluation may show the general metastatic context if positive or it may suggest the thyroid origin especially in patients with prior thyroidectomy and a certain disease free interval (28,29,30). Overall, histological report, radioiodine uptake at scintigraphy or high circulating thyroglobulin of otherwise unexplained source are the best assessments for an adequate diagnosis and further therapy even the general prognosis is considered severe in this cases (28,29,30).…”
Section: Incidental Findingsmentioning
confidence: 99%